The Impact of Infrastructural Facilities on the Poverty of Farmers in Bidur Municipality, Nepal. - Udaya Ranamagar (Hasanuddin University, 2013)
Poverty is one of the major problems in Bidur Municipality, Nepal. The municipality has higher rate of poverty compared to the other municipalities. The municipality has been suffering from poor infrastructural facilities. Therefore, this study identifies the significant aspect of infrastructures which might affect poverty. Since the concept of poverty is broad and has been discussed from many perspectives, the per capita income was taken to identify poverty in this study. Correlation and Multiple Regression Analysis were employed. Results showed that 30% of the people lived below the poverty line, which is higher than national urban poverty. Among the different infrastructural facilities, paved roads were found to be the most dominating factor that has an impact on the poverty in the Municipalities. However, other influencing factors such as vocational training and employment in non–agricultural sector were also significant in improving the poverty line of farmers in the municipality. Future research should be focused on studying the impact of paved road construction in other municipalities that may help to reduce poverty within the farmer’s community when more economic opportunities are created.